Gen Z digital behaviour: The role of consumer style inventory and eWOM in accommodation booking intention - Anindita Dwi Wulandari; Ahmad Hudaiby Galih Kusumah (International Journal of Applied Sciences in Tourism and Events, 2026)
Generation Z shows a high dependence on online reviews and recommendations (eWOM) as a primary reference in purchasing decisions, particularly in the context of accommodation selection. This study aims to examine the decision-making styles of Generation Z consumers, as conceptualized within the Consumer Style Inventory (CSI) framework, and to examine how these styles influence the use of electronic word-of-mouth (eWOM) in accommodation selection, as well as their relationship with purchase intention. Data collection was conducted through a questionnaire distributed via social media. This study used Structural Equation Modelling (SEM) SmartPLS to analyse data collected from 220 Generation Z respondents. The results show that recreational attitude significantly influences eWOM use intention, while eWOM use intention positively affects purchase intention in accommodation booking decisions. These findings indicate that consumers who perceive eWOM activities as enjoyable are more likely to engage with online reviews before making accommodation-related decisions.